Elaboracion Del Manual De Funciones Y Procedimientos Para El Cargo Analista De Importaciones En Agencia De Aduanas Mag Customs Nivel 2 - Chaves Gómez, Yennifer (Universidad Antonio Nariño, 2023)
The purpose of this internship is to prepare the manual of functions and procedures for improve the performance and understanding of the process of import analysts in the Agency of Customs Mag Customs Level 2 because there is no precedent or document that complies with these characteristics. Leaving in evidence the low performance of the staff, the multiple setbacks and cost overruns in customs processes; it is there where it is intended to contribute a consultation mechanism such as research and training for the competitive development of the professional within the company.